2020
DOI: 10.1007/s13233-020-8080-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Program for Analyzing Dielectric Relaxation and Its Application to Polymers: Nitrile Butadiene Rubber

Abstract: To characterize the dielectric relaxation embedded in polymers, we developed a program algorithm that analyzes the relaxation processes from dielectric permittivity versus frequency data based on governing functions such as the Havriliak-Negami function including the conductivity contribution. With the help of the developed simulation program, we have identified three processes: an α process due to rotational and segmental motions of the C-C bond, an α' process attributed to the fluctuation of the end-to-end d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…The study of the polymer solution in Reference 161 showed that water clustering is likely to occur at high polymer concentrations, substantially affecting the DR processes. A recent study in Reference 163 developed a novel program algorithm that supports the analyzing of DR based on data from the DRS method. Relying on the Havriliak–Negami function, the algorithm identified DR modes or processes due to the segmental motions, end‐to‐end polymer chain fluctuations, and conduction contribution.…”
Section: Dielectric Relaxation For Pilsmentioning
confidence: 99%
“…The study of the polymer solution in Reference 161 showed that water clustering is likely to occur at high polymer concentrations, substantially affecting the DR processes. A recent study in Reference 163 developed a novel program algorithm that supports the analyzing of DR based on data from the DRS method. Relying on the Havriliak–Negami function, the algorithm identified DR modes or processes due to the segmental motions, end‐to‐end polymer chain fluctuations, and conduction contribution.…”
Section: Dielectric Relaxation For Pilsmentioning
confidence: 99%
“…e present work was performed for NBR specimens produced from both different batches and compositions in [23]. Furthermore, this research is extended to lower frequencies reaching 0.01 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…is work decomposes the superimposed dielectric spectrum and assigns the peaks of the relaxation processes in the dielectric spectrum, resulting in the characterization of several relaxation processes with a developed dispersion analysis program [23]. e upgraded algorithm is used to analyze the relaxation processes by selectively satisfying either real or imaginary dielectric data based on three governing functions-the Cole and Cole [24], Davidson and Cole [25], and HN [26] functions-together with the conduction contribution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation